Testing and Comparing the Causal Relationship between Health Control Center and Health-Related Quality of Life Mediated by Diabetic Psychological Distress among Patients with Type 1 and 2 Diabetes - Ismail Bahreini; Saeed Bakhtiarpour; Parvin Ehteshamzadeh; Alireza Heidari (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: Diabetes can have significant psychological effects on health and delay the disease's recovery. Therefore, the aim of this study was to test and compare the causal relationship between the health control center and health-related quality of life mediated by diabetic distress in patients with type 1 and type 2 diabetes. Materials and Methods: This study was conducted with the participation of 371 patients with type 1 and type 2 diabetes who were referred to endocrinologists in Bushehr in 2019, and were selected by convenience sampling method. Data were collected via Health-related Quality of Life, Psychiatric Distress of Diabetic Patients, and Health Control Center questionnaires. Data were analyzed via the path analysis method using AMOS software version 22. Results: In the group with type 1 diabetes, with increasing of health control center related to influential people with a mean (SD) of 28.1 (3.2) and increasing the internal health control center with a mean (SD) of 23.1 (3.1), health-related quality of life increases with a mean (SD) of 40.1 (7.1) (P<0.001). However, with the increase of the health control center related to chance with a mean (SD) of 24.00 (8.7), the quality of life-related to health decreases (P<0.001). Also, with the increase of the health control center related to influential people and the internal health control center, diabetic distress decreases with a mean (SD) of 2.8 (0.9) (P<0.001). Diabetic distress increases as the chance related health control center increases (P<0.001). Also, with increasing diabetic distress, the quality of life-related to health decreases (P<0.001).  In the group of type 2 diabetes, with increasing the health control center related to influential people with a mean (SD) of 26.3 (4.3) and increasing the internal health control center with a mean (SD) of 25.1 (7.1), health-related quality of life increases with a mean (SD) of 43.2 (12.1) (P<0.001). However, with increasing the health control center related to chance with a mean (SD) of 20.3 (6.6), the quality of life-related to health decreases (P<0.001). Also, with the increase of the health control center related to influential people and the internal health control center, diabetic distress decreases with a mean (SD) of 2.6 (0.8) (P<0.001). Diabetic distress increases as the chance related health control center increases (P<0.001). Also, with increasing diabetic distress, the quality of life-related to health decreases (P<0.001). Conclusion: The study showed that the health control center had a significant correlation between chance and related people with health-related quality of life. Internal Health Control Center, in addition to having a direct impact on the quality of life, also reduces the quality of life in both groups of patients with type 1 and type 2 diabetes by reducing the anxiety of diabetes.